Sharing the Ideas of Meta – Science to Improve Quality of Research - Aryal, UR; Khanal, K (Kathmandu University Medical Journal, 2014)
Meta-Science is an interdisciplinary science which provides plenty of oppurtunity to cooperate on better understanding of micro-social dimension of science. It plays vital role to justify the conclusion, which helps to improve quality of research as well as to health services. There are various applications of meta-science for improving quality of research namely: applying theories of philosophy and different disciplines, the use of triangulation, inductive and deductive reasoning, ethical issues and finally fundamentals of scientific research. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11032 Kathmandu University Medical Journal Vol.11(1) 2013: 75-77